Productivity outcomes in online labor markets and within-task complexity and difficultly - Evaggelos Mourelatos; Nicholas Giannakopoulos; Manolis Tzagarakis (Global Labor Organization (GLO), 2020)
We analyze the impact of within-task difficulty and complexity on workers' productivity in online labor markets. Using a randomized control quasi-experiment in AMT we are able to define the difficulty and complexity embodied in requested sub-tasks within a problem-solved task. We find that our productivity measures are negatively related to the difficulty and complexity of a specific sub-task. This finding is robust to several sources of workers' heterogeneity and to different pay schemes.
Keywords: J24; D90; 330; Productivity; Online Labor markets; Task Difficulty and Complexity